Male and female (in)tolerance profile in regard to living with diversity in a southern brazilian community - Mário Antonio Sanches; Clara Nasser Scherer; Giovana Maestrelli (SER Social)
This article examines parents’ (in)tolerance in recommending or not their children’s coexistence with people situated in a wide diversity range. It is an exploratory research, conducted in a southern Brazilian community, by use of a questionnaire, with 225 participants. The analysed questions started with the sentence: “how do you position yourself when your son or daughter seeks to live with people of the opposite sex, another religion, other ethnicities or races, another social class, with disabilities, homosexuals and children of prisoners?”. The analysed results focus on the different postures taken by female and male participants of the sample. The research shows that the female sample appeared to be more prone to encourage coexistence with the multiple categories of people investigated. The study is relevant to understand that living with diversity reveals distinct world views from the female and male populations.